Predictive Factors of Smoking among Adults Based on Trans-theoretical Model - Masoomeh Bagheri; Nasrin Roozbahani; Mohsen Shamsi (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective:It is necessary to identify factors influencing smok-ing in order to design effective interventions to reduce this behavior. This study aimed to determine the predictive factors of smoking among adults of Arak city based on Transtheoretical model (TTM). Methods:This analytical- cross sectional study was carried out on 328 smokers 30 years of age and older in the city of Arak in 2014. Samples were selected randomly from family file numbers of Arak. Data were collected using a valid and reliable questionnaire including demographic information and questions related to Transtheoretical structure Model (stages of change, processes of change, temptation, Pros and Cons of smoking) and were analyzed using one-way ANOVA, Pearson correlation and linear regression. Results: Most of the subjects (52.7%) were in the precontemplation stage of smoking cessation. Linear regression revealed that variables of change stages (R2 = -0.46, p > 0.001), temptation (R2 = -0.18, p > 0.001), hazards of smoking (R2 = -0.12, p > 0.001), early age of smoking (R2 = -0.14, p > 0.006), dramatic relief process of change (R2 = -0.12, p > 0.015) and the number of friends who smoke (R2 = -0.12, p > 0.048) were the predictor of daily smoking rates. The model was able to predict 37% of smoking rate variance. Conclusion: Most subjects were in the precontemplation stage of quitting smoking and according to predictive factors of smoking it is necessary to plan an effective educational program for quitting smoking.Paper